The Flapping Motion of Mercury's Magnetotail Current Sheet: MESSENGER Observations. Issue 4 (19th February 2020) - Zhang, C.; Rong, Z. J.; Gao, J. W.; Zhong, J.; Chai, L. H.; Wei, Y.; Shen, C.; Wan, W. X.
Abstract: The flapping motion of Mercury's magnetotail current sheet is investigated based on the observations of MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER). The typical flapping period in Mercury's magnetotail is much shorter (~13 s), comparing with ~10–20 min at Earth's magnetotail. The magnetic field oscillation amplitude induced by flapping motion is larger near both flanks than that around tail center. Similar to Earth's magnetotail, there are two flapping types existent in Mercury's magnetotail, one is the kink‐like flapping that can propagate as traveling waves, and the other one is the steady flapping that does not propagate. Both flapping types distribute widely in magnetotail. The kink‐like flapping waves propagating either dawnward or duskward can be observed across the entire magnetotail current sheet, which suggests that the energy sources for triggering the kink‐like flapping waves should locate around both tail flanks instead of tail center as is for the Earth's magnetotail. Plain Language Summary: The tail‐flapping motion is a fundamental dynamic activity of planetary magnetotail, which has been studied widely in terrestrial planets except for Mercury. The tail‐flapping motion plays an important role in dissipating the energy stored in magnetotail and has two types according to previous studies, that is, steady flapping and kink‐like flapping. To understand the flapping physics generally, studies on the flapping motion of different planets with identified types have been conducted recently. In order to continue study of the planetary tail flapping motion, here, with a state‐of‐the‐art analysis technique, we study the flapping motion of Mercury's magnetotail based on the 4‐year measurements of MESSENGER. The derived results demonstrate that the flapping pattern of Mercury's tail is similar to that of Venusian/Martian tail, but different with Earth's magnetotail, though Mercury also possesses an intrinsic dipole magnetosphere. Key Points: The flapping motions of Mercury's magnetotail are investigated based on MESSENGER's observations for the first time The flapping period is much shorter compared with that of Earth's magnetotail Like Venus and Mars, the energy sources inducing the kink‐like flapping motion are probably located near both flanks of magnetotail